Disability Embodiment, Speculative Fiction, and the Testbed of Futurity. Issue 1 (1st February 2022) - Murray, Stuart
Abstract : The article analyses depictions of disability embodiment in a range of contemporary North American speculative fiction that depicts post-crisis worlds of social and environmental breakdown. It argues that in each novel bodies are threatened and placed under pressure, particularly in terms of capacity and function. While some resolve this through recourse to humanist narratives of restitution, others imagine futures in which both bodies and societies become reformatted. Bodies remain material, but they also become metamorphized and messy; they hold charged manifestations of personhood, but also leak these conceptions of "person;" they are recognizably human, but also patterned as posthuman. The results are depictions of disability-led embodiment that, precisely because they are formed in imagined possibilities of the future, offer productive possibilities for re-visioning the present.